Fruit phenology of citruses, mangos and papayas influences egglaying preferences of Bactrocera invadens (Diptera: Tephritidae) - Diatta, P.; Rey, J.; Vayssières, Jean-François; Diarra, K.; Coly, E.V.; Lechaudel, M.; Grechi, I.; Ndiaye, S.; Ndiaye, O. (EDP Sciences, 2013)
Introduction. African fruit production, as well as regional and international fruit trade,have experienced heavy economic losses over the past decade due to the damage caused by fruitflies, especially B. invadens Drew Tsuruta & White (Tephritidae: Diptera). Bactrocera invadensattacks fruits belonging to numerous botanical families, several of which are of great economicimportance. The females of these flies generally lay their eggs in mature fruits, but some can layin green-immature fruits. Materials and methods. The influence of the species, variety andphenology of fruits on the fruit attractiveness to B. invadens and the elicitation of B. invadens egglayingbehaviour were studied in the laboratory. Fruits harvested regularly during the years 2008and 2009 from orchards in the Niayes area (Senegal) were exposed to gravid females in cages setfor the different factors tested. The exposed fruits were then incubated and the pupae emergingfrom them were counted. Results and discussion. Bactrocera invadens females laid eggs in ripefruits. Within the same fruit species, the variety plays an important role in egg-laying preference.Hence, among the mango varieties tested, the Pêche variety hosted the highest number of pupaeper fruit, while the Palmer variety hosted the lowest number. Comparison among different fruitspecies showed that mature papaya was more infested than mature mango or citrus. Furthermore,flies were unable to develop on lime. Conclusion. Our study showed that B. invadens can infestgreen and ripe host fruits, and even immature abscised fruits. Consequently, management of thispest must include preventive measures in the development and implementation of an integratedmanagement system.